Regional and Temporal Trends in Migration among People Living with HIV/AIDS in British Columbia, 1993-2005 - Lima, Viviane D. (Can J Public Health, 2010)
OBJECTIVES: To examine regional and temporal trends in migration among patients receiving HIV treatment in British Columbia (BC). METHODS: Patients initiating antiretroviral therapy in BC between January 1993 and November 2004 were followed until November 2005. Migration was calculated as the cumulative number of times a patient’s residential address changed during their course of treatment. Analyses were performed at the provincial and at the regional health authority (HA) and local health area levels. Demographic methods were used to estimate the in- and out-migration rates, indices of dissimilarity and concentration across regions over time. RESULTS: A total of 3,588 participants were followed during the study period. Individuals who migrated most often migrated to the Vancouver Coastal HA (from the Interior: 30%, Fraser: 41%, Vancouver Island: 28%, and Northern: 19%), specifically the city of Vancouver, which has been treating the most patients with HIV since the early stages of the epidemic. We also showed that this movement intensified as more contemporary HAART regimens became available (p-value for trend <0.01). DISCUSSION: Our results demonstrate that migration among people with HIV in BC is not homogeneous, with areas around large urban centres having the highest influx of patients. It is thus important that health authorities in BC work in partnership to monitor and evaluate accessibility of HIV-related health care services to ensure universal access for all patients. Furthermore, enhanced HIV care and support services need to be developed, on a province-wide basis, and funding allocation needs to be adjusted to reflect patient migration in BC.